The Role of Guru Belajar Nusantara Community in Improving Teacher Competence - Sunarko, Moh. Heru; Musytamil, Khusni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
The enhancement of teacher competence is a crucial responsibility that lies with the educators themselves. Given the ever-evolving challenges faced by students, including learning difficulties, bullying, and issues like sexual harassment, it becomes imperative for teachers to continually upgrade their skills and knowledge. This study aims to explore the pivotal role played by the Guru Belajar Nusantara community in Pekalongan in the advancement of teacher competence. This research adopts a qualitative approach, employing a case study research type to delve into the subject matter. The findings of this study highlight several key aspects: Advocating for Teacher Independence: The Guru Belajar Nusantara community in Pekalongan actively contributes to the cause of teacher independence. By supporting teachers' autonomy in their professional development, they help enhance their pedagogical competence and overall professionalism. Fostering Competence Development: The community ensures that every teacher has equitable opportunities to enhance their competence. This commitment to professional growth is instrumental in improving the pedagogical competence of teachers and elevating their professionalism. Facilitating Collaborative Empowerment: The Guru Belajar Nusantara community in Pekalongan actively engages in empowering teachers through diverse collaborations. This collaborative approach plays a significant role in boosting teachers' social competence, enabling them to navigate the complexities of the educational landscape more effectively. In summary, this research underscores the critical role played by the Guru Belajar Nusantara community in Pekalongan in championing teacher independence, fostering competence development, and facilitating collaborative empowerment. These endeavors collectively contribute to improving the overall competence and professionalism of teachers in the Pekalongan region.